2007
DOI: 10.1159/000100793
|View full text |Cite
|
Sign up to set email alerts
|

Pregnancy on Intensified Hemodialysis: Fetal Surveillance and Perinatal Outcome

Abstract: Objectives: To evaluate the effect of intensive fetal surveillance via Doppler ultrasound and fetal non-stress test on the perinatal outcome of pregnant women undergoing an intensified hemofiltration scheme. Methods: Five consecutive pregnancies of women undergoing intensified hemodialysis were analyzed due to the following parameters: maternal background, hemodialysis schedule during pregnancy, blood pressure, occurrence of fetal complications, occurrence of obstetric complications, gestational week at delive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
1
8

Year Published

2009
2009
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 45 publications
0
24
1
8
Order By: Relevance
“…Although prematurity is very likely, a large proportion do progress to a satisfactory duration. Other studies from the recent era report a median GA of 31-33 weeks (2,6,9,10,20), with superior GA in patients treated with nocturnal hemodialysis (16,18). Most infants born were of low BW (,2500 g), which correlated with prematurity, although a large proportion of babies were on or below the 10th centile of weight for GA. Our median BW was similar to that in other recent studies, which reported median or mean BW ranging from 1483 to 1765 g (6)(7)(8)(9)(10)20), but it remains substantially less than the mean BW (6 SD) of 2417.56657 g reported in pregnancies managed with nocturnal hemodialysis (16).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Although prematurity is very likely, a large proportion do progress to a satisfactory duration. Other studies from the recent era report a median GA of 31-33 weeks (2,6,9,10,20), with superior GA in patients treated with nocturnal hemodialysis (16,18). Most infants born were of low BW (,2500 g), which correlated with prematurity, although a large proportion of babies were on or below the 10th centile of weight for GA. Our median BW was similar to that in other recent studies, which reported median or mean BW ranging from 1483 to 1765 g (6)(7)(8)(9)(10)20), but it remains substantially less than the mean BW (6 SD) of 2417.56657 g reported in pregnancies managed with nocturnal hemodialysis (16).…”
Section: Discussionmentioning
confidence: 95%
“…However, given prolonged waiting times for organs, this may occur after the reproductive years have passed. With studies such as ours demonstrating improved outcomes for women with CKD who commence dialysis in pregnancy, as well as the growing body of evidence regarding intensive dialysis regimens to improve outcomes (6)(7)(8)(9)(10)16), there may be a shift in the way women are counseled regarding pregnancy on dialysis, toward a less discouraging attitude (2). This may provide an avenue for motherhood in women who otherwise may not have an opportunity.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In light of the heterogeneity of the data, any attempt to correlate outcomes with dialysis therapy is hazardous; however, that the best results are reported in settings of long daily dialysis suggests that dialysis efficiency plays an important role. More in detail, the three series that were free of neonatal death and stillbirth are those that used the longest and most intensive treatments (long nightly dialysis and "as much dialysis as the patients could tolerate") (5,15,17). These account for 15 of 15 live infants of 16 conceptions (one elective termination), which is a favorable outcome in comparison with the 46 of 60 live infants with the other dialysis schedules, although the difference does not reach statistical significance (P ϭ 0.059).…”
Section: Discussionmentioning
confidence: 99%